2013
DOI: 10.1136/bcr-2013-200283
|View full text |Cite
|
Sign up to set email alerts
|

Ileal atresia secondary to antenatal strangulation of Littre's hernia in an exomphalos minor

Abstract: SUMMARYWe describe an unusual case of ileal atresia, resulting from antenatal strangulation of a Meckel's diverticulum in an exomphalos minor. This is a rare antenatal complication of Littre's hernia, which has not been previously described. A small exomphalos minor at the base of umbilical cord and late onset vascular accident at the narrow defect leading to ileal atresia may be missed in the prenatal diagnosis. The triad of exomphalos minor, Meckel's diverticulum and terminal ileal atresia secondary to anten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…capable of intestinal and mesenteric compression by the interruption of blood supply resulting in ischemia [4,5]. Pratap et al [6] described a case of ileum entrapped within the omphalic ring and that entrapped segment of ileum was atretic. Patel et al [6] reported an unusual case of ileal atresia resulting from antenatal strangulation of Meckels diverticulum in omphalocele minor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…capable of intestinal and mesenteric compression by the interruption of blood supply resulting in ischemia [4,5]. Pratap et al [6] described a case of ileum entrapped within the omphalic ring and that entrapped segment of ileum was atretic. Patel et al [6] reported an unusual case of ileal atresia resulting from antenatal strangulation of Meckels diverticulum in omphalocele minor.…”
Section: Discussionmentioning
confidence: 99%
“…Pratap et al [6] described a case of ileum entrapped within the omphalic ring and that entrapped segment of ileum was atretic. Patel et al [6] reported an unusual case of ileal atresia resulting from antenatal strangulation of Meckels diverticulum in omphalocele minor. The first association of ileal atresia with Omphalocele minor is the single isolated type.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that small omphalocele associated with noncardiac anomalies has overall good prognosis [19][20][21] (Figure 2). Patients with small omphalocele have fewer cardiac defects, which may explain their better prognosis as severe cardiac defects portend poorer prognosis.…”
Section: Discussionmentioning
confidence: 99%